Bisnis Multi Level Marketing Pada PT. K-Link Nusantara Di Tinjau Dari Hukum Bisnis Islam - Nurhasanah, Siti; Taufik, Sulamat (Kopertais Wilayah I DKI Jakarta dan Banten, 2020)
The purpose of this research is to discuss the multi level marketing (MLM) business in terms of Islamic business law, as well as to find out how the business practices carried out by PT. K-LINK and whether K-Link's MLM business practices are in accordance with the DSN-MUI fatwa No 75 / DSN-MUI / VII / 2009. This study used descriptive qualitative method. The data collection techniques used interviews and documentation. Based on the research results it is known that the Multi Level Marketing business practices at PT. K-Link Nusantara, starting from its direct selling practice, marketing and recruiting, bonus distribution and prices have followed the existing Islamic law rules and can be said to be in accordance with the basic principles of the Islamic religion which refers to the Al-Quran, Hadith, and Ijma '. And the MLM business practices of PT. K-Link Nusantara is protected from something that is forbidden such as maisir, ghoror, haram, usury, indecency, dzulm and immorality. The aqad uses aqad al-bai '/ murabahah, aqad wakalah, aqad ju'alah, and aqad ujroh. All of these aqads are adjusted to the contents of the DSN-MUI fatwa Number 75 / DSN-MUI / VII / 2009 concerning the Guidelines for Direct Selling in Sharia Level, so the practice can be said to be in accordance with the DSN-MUI fatwa Number 75 / DSN-MUI / VII / 2009.